Writing case reports and series: Tricks, traps, and triumphs! - Abraham Edgar Gracia-Ramos (Indian Journal of Rheumatology)
The case reports and case series are the oldest genres of medical literature. They constitute uncontrolled study designs with different varieties that describe important scientific observations that are missed or undetectable in other research methods. The advantages of employing case reporting include the discovery of unusual clinical conditions or unrecognized diseases, the detection of beneficial or side effects of treatments, the exploration of alternatives in clinical practice, solving ethical limitations, formulation of hypotheses, teaching, and the opportunity to generate publications. On the other hand, they have several shortcomings that limit their credibility such as the impossibility to generalize their findings, selection and recall bias, information preferences, overinterpretation (“anecdotal fallacy”), and the distraction of readers toward the unusual. The journey toward publishing a case study begins with the choice of the case, followed by an in-depth literature review on the issue. Obtaining the signed consent of the patients or their representatives and the selection of the journal for the publication of the article are the next steps. Writing a structured report may vary, but it can generally be represented by the acronym SIPDiSC: Summary (abstract), Introduction, Presentation, Discussion, Summary of the case experience, and Conclusion. Finally, a careful choice of authors should be made. Writing high-quality case reports and case series provides valuable information for clinical research, clinical practice, and medical education.